The concept of therapy of patients with sensory-motor aphasia - Goralewska, Magdalena; Garczyński, Wojciech; Gębska, Magdalena; Ciosek, Żaneta (Journal of Education, Health and Sport, 2018)
Summary. In Poland, every year suffer a stroke about 70 thousand. people every year this number increases. Stroke is the third leading cause of death among adults in Poland, right after heart disease and cancer. Statistically, the number of people who experience a stroke, is similar in almost all over Europe, but in our country in comparison with the countries of Western Europe often death occurs as a result of stroke or permanent disability. This is related to the health condition of our society, with concomitant diseases, but above all, the difficulties with diagnosis quick and very little access to complex therapy in the first, acute phase after the onset of stroke. A significant proportion of patients experiencing post-stroke speech disorders and / or understanding of, on average, it is estimated that every third person after a stroke is diagnosed aphasia. Appointment of the National Program for Prevention and Treatment of Stroke, which seeks to modernize the branches of neurological rehabilitation and the creation of a system of neurological rehabilitation on an outpatient basis, to contribute to the better functioning of the impact of the incident. Currently, about 70% of patients after stroke disability remains, which increases the likelihood of post-stroke depressive disorder (PSD). Stroke, in conjunction with physical disabilities, communication disorders, permanently life-changing, not only the patient, but also families. Dependence on other people, abnormal functioning in the accompanying next of said depression can lead to outbursts of anger, decrease in self-esteem. The proper operation of therapy.